(3GdJjSjQ aj Yde GdJaSjQs - (3eMeO Hf SdjeGf Hf SYO Hf eSYhO GdcGajLj GdQhej GdMfaj, eMjj GdOjf, CHh YHO Gddg, J (B879 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CfRd GdbQBf CeG HYO aEf eOGQ GdTQGFY hGdESdGe cdGe Gddg Gdedc GdYdGe hGQOJ JOhjfg HbOQ GdhSY hGdEecGf , QJHJ gPg GdQSGdI Ydi HGHjf hNGJeI GdHGH GdChd ai GdEUWdGMGJ s
(3BNQgG (B:s
(3GdbSe GdKGfi hgh GdESJOdGd HGdCTcGd Ydi GdGMhGd s
(3CdaI GdeDda YGe (B856(3g`s
(3jdi GdeNWhW fbhd ai Yde GdJaSjQs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B51 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B209s
Keywords: (3GdJaSjQ hYdhe GdbQBfs